2014
DOI: 10.3402/meo.v19.23646
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cognitive biases and biostatistics knowledge of medical residents: a multicenter, cross-sectional questionnaire study

Abstract: PurposeThe aim of this study is to determine the perceived familiarity of medical residents with statistical concepts, assess their ability to integrate these concepts in clinical scenarios, and investigate their susceptibility to the gambler’s fallacy and the conjunction fallacy.MethodsA multi-institutional, cross-sectional survey of Greek medical residents was performed. Participants were asked to indicate their familiarity with basic statistical concepts and answer clinically oriented questions designed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 41 publications
4
34
1
4
Order By: Relevance
“…Second, similar studies among other specialties have yielded consistent results with similarly sized samples. 16,[19][20][21] This latter observation suggests that the core deficiency is not necessarily with plastic surgery training, but with postgraduate health professions training in general, regardless of graduate field (medicine, dentistry, pharmacy). In addition, the resident demographics of the respondents suggest a higher proportion of integrated respondents than the population at large and a greater proportion of respondents with advanced degrees, compared to the population at large (22% vs approximately 10%).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Second, similar studies among other specialties have yielded consistent results with similarly sized samples. 16,[19][20][21] This latter observation suggests that the core deficiency is not necessarily with plastic surgery training, but with postgraduate health professions training in general, regardless of graduate field (medicine, dentistry, pharmacy). In addition, the resident demographics of the respondents suggest a higher proportion of integrated respondents than the population at large and a greater proportion of respondents with advanced degrees, compared to the population at large (22% vs approximately 10%).…”
Section: Discussionmentioning
confidence: 90%
“…[14][15][16][17][18][19][20][21][22] Even among those with formal training in biostatistics or epidemiology, there was a poor understanding of frequently used statistical tests and a limited ability to correctly interpret the results and identify the associated limitations. With the increasing volume and complexity of statistical data presented in journal articles, it is possible that practitioners with limited knowledge of biostatistics will have increasing difficulty with interpreting the results of current studies.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Only three manuscripts evaluated more than 5 cognitive biases in the same study, in-line with the narrow scope of most studies [39, 50, 52]. One third of studies ( n  = 6) were descriptive, i.e., they provided the frequency of the cognitive bias without outcome data [36, 37, 39, 44, 48, 51]. …”
Section: Resultsmentioning
confidence: 96%
“…Moreover, across studies we often found a lack (in 30 % of studies) or heterogeneity in the outcome measures, mixed denominators (some studies report their findings based on the number of participants, while others based on case-scenarios) [41, 43, 52], and different scope (e.g. some studies are descriptive, [36, 37, 39, 44, 48, 51] whereas others [7, 30, 35, 42, 43, 47, 50, 52] target diagnostic or therapeutic errors). Third, most studies use hypothetical case-vignettes which may not truly reflect medical decisions in real life.…”
Section: Discussionmentioning
confidence: 99%